2003
DOI: 10.1086/346107
|View full text |Cite
|
Sign up to set email alerts
|

Polar Ring Galaxies and the Tully‐Fisher Relation: Implications for the Dark Halo Shape

Abstract: We have investigated the Tully-Fisher relation for polar ring galaxies (PRGs), based on near-infrared, optical, and H i data available for a sample of these peculiar objects. The total K-band luminosity, which mainly comes from the central host galaxy, and the measured H i line width at 20% of the peak line flux density, which traces the potential in the polar plane, place most polar rings in the sample far from the TullyFisher relation defined for spiral galaxies, with many PRGs showing larger H i line widths… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
87
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 58 publications
10
87
1
Order By: Relevance
“…The dark-to-visible mass ratio in PRGs is again not larger than in spiral galaxies. Iodice et al (2003) have shown that polar ring velocities are abnormally large, when compared to the Tully-Fisher relation for spiral galaxies. The dark halo could then be either flattened along the polar ring, or spheroidal and very massive: the dark-to-visible mass ratio inside the optical radius would be as large as 3.5.…”
Section: Dark Matter Around Polar Ring Galaxiesmentioning
confidence: 95%
“…The dark-to-visible mass ratio in PRGs is again not larger than in spiral galaxies. Iodice et al (2003) have shown that polar ring velocities are abnormally large, when compared to the Tully-Fisher relation for spiral galaxies. The dark halo could then be either flattened along the polar ring, or spheroidal and very massive: the dark-to-visible mass ratio inside the optical radius would be as large as 3.5.…”
Section: Dark Matter Around Polar Ring Galaxiesmentioning
confidence: 95%
“…NGC 6822 can therefore be considered to be a polar ring galaxy (PRG). Investigators of PRGs have found that almost all of these systems exhibit evidence of recent formation, possibly within the past 2 Gyr (Whitmore et al 1990;Iodice et al 2003). If this is also the case of NGC 6822, we need to identify the interaction that may have triggered a burst of star formation.…”
Section: Age Distributionmentioning
confidence: 99%
“…On longer timescales, the polar ring can become warped or unstable. Moreover, some observations [29] suggest that the velocity field of some polar ring galaxies is consistent with a flattened dark matter halo, along the plane of the polar ring. Our simulations show that stable polar rings form also if the dark matter halo is spherical.…”
Section: Gas Ringsmentioning
confidence: 98%